- #1

- 6

- 0

- Thread starter QUBStudent
- Start date

- #1

- 6

- 0

- #2

arildno

Science Advisor

Homework Helper

Gold Member

Dearly Missed

- 9,970

- 132

Suppose that, for a particular choice of x, f(x)>=g(x).

Then, |f-g|=f-g, from which follows that M(x)=f(x).

If g(x)>=f(x), then |f-g|=g-f, that is, M(x)=g(x)

- #3

- 6

- 0

cool thnx for the response

- Last Post

- Replies
- 4

- Views
- 12K

- Last Post

- Replies
- 2

- Views
- 9K

- Last Post

- Replies
- 1

- Views
- 2K

- Replies
- 7

- Views
- 617

- Last Post

- Replies
- 4

- Views
- 9K

- Last Post

- Replies
- 2

- Views
- 1K

- Last Post

- Replies
- 1

- Views
- 1K

- Last Post

- Replies
- 2

- Views
- 2K

- Replies
- 3

- Views
- 2K

- Last Post

- Replies
- 16

- Views
- 5K